History of inclusive physical education in South America - Mauerberg-deCastro, Eliane [UNESP]; Campbell, Debra Frances [UNESP] (My University, 2019)
We examined how the origins of education and special education have influenced inclusion in schools and in physical education (PE) in the South American region. National and constitutional legislation in every country in the region has followed international recommendations (e.g., the many campaigns and directives from the United Nations and others), which, therefore, has helped to reform school curricula provisions and bylaws for the inclusive education of people with disability (PWD). However, for these countries, the reality of opportunities for education in general has evolved in unique directions due to the political and cultural influences of their institutions, educators and societies in general. Pedagogic practices for successful inclusion in schools are still unknown in the region. The statistics of some countries show an increase in enrolment rates over the course of decades after educational reforms had taken place. Lack of accountability for ensuring school retention and achievement for PWD has resulted in a negatively biased perception of the value of inclusive settings. As for PE in regular schools, teachers who are unprepared and potentially confused about how to merge rehabilitation procedures with pedagogical practices reveal little evidence that the discipline has evolved in the region. Teacher preparation in PE higher education continues to include adapted physical education (APE) programmes designed for segregated settings: one for each disability.